Síntese, caracterização e estudo das propriedades fotoeletrocatalíticas dos fotoanodos BiVO4 e BiVO4/FeOOH - Araújo, Moisés Albuquerque de (Universidade Federal de São Carlos, 2015)
Among the variety of semiconductor materials investigated to apply in electrochemical cells bismuth vanadate (BiVO4) is one of the candidate which would be used as photoanode. Thus, this study aimed to synthesize thin films of BiVO4 and their modification with a thin layer of iron (III) oxyhydroxide (FeOOH) by photodeposition and study their photoelectrocatalytic properties. The optimization of BiVO4 synthesis condition was assessed by a factorial design 23 and an analysis of univariate type. The parameters studied were annealing temperature (500 and 600 °C), calcinations time (30, 60, 150 and 270 min.), solvent type employed for dissolving the BiVO4 precursor reagents (poly ethylene glycol 300-PEG 300, PEG 400, ethylene glycol-EG, mixture 1:1 by volume of PEG 300 and EG), deposition method of BiVO4 films (dropping and spin coating) and method of drying layers (heating at 500 °C, heat gun and no drying). From the optimized condition BiVO4 film was prepared by dissolving bismuth (III) nitrate and ammonium metavanadate in a mixture of 1:1 by volume of EG and PEG 300, it was deposited onto glass containing FTO by spin coating and then calcinated directly at 500 °C for 60 min. The photodeposition was carried out in the mixture FeSO4 and sodium citrate medium both 1 mmol L-1 and pH 4.7 by applying the open circuit potential for 5 min. and under light incidence. and then polarizing at 1.2 V for 1 min. BiVO4 and BiVO4/FeOOH films were characterized by XRD, SEM, EDS, UV-vis, voltammetry (cyclic and linear) and electrochemical impedance spectroscopy. The results reveled that photocurrent values increased 2.5 times at 0.71 V and the on set potential shifted to less positive value in the presence of FeOOH, also there was a considerable reduction of the charge transfer resistance in the interface photoanode/solution. The bare BiVO4 films were photostable during the illumination time studied which was 4 h. However, the modified films did not show the same behavior, the photocurrent value decreased 29% after 4 h illuminated. The results in the sulphite presence showed that photocurrent value for bare BiVO4 and BiVO4/FeOOH were less than the maximum photocurrent value which would achieve for this materias.
SYNTHESIS, CHARACTERIZATION AND STUDY OF PHOTOELECTROCATALYTIC PROPERTIES OF PHOTOANODES BiVO4 AND BiVO4/FeOOH
Keywords: Vanadato de bismuto; Oxihidróxido de ferro (III); Células fotoeletroquímicas; Fotoeletrocatálise; Bismuth vanadate; Iron (III) oxyhydroxide; Photoelectrochemical cells; Photoelectrocatalysis; CIENCIAS EXATAS E DA TERRA